The role of hydrodynamic stress on the phenotypic characteristics of single and binary biofilms of Pseudomonas fluorescens - Simões, M. (2007)
This study investigates the phenotype of turbulent (Re=5,200) and laminar (Re=2,000) flowgenerated Pseudomonas fluorescens biofilms. Three P. fluorescens strains, the type strain ATCC 13525 and two strains isolated from an industrial processing plant, D3-348 and D3-350, were used throughout this study. The isolated strains were used to form single and binary biofilms. The biofilm physiology (metabolic activity, cellular density, mass, extracellular polymeric substances, structural characteristics and outer membrane proteins [OMP] expression) was compared. The results indicate that, for every situation, turbulent flow-generated biofilms were more active ( p <0.05), had more mass per cm2 ( p<0.05), a higher cellular density ( p <0.05), distinct morphology, similar matrix proteins ( p>0.1) and identical (isolated strains – single and binary biofilms) and higher (type strain) matrix polysaccharides contents ( p<0.05) than laminar flow-generated biofilms. Flow-generated biofilms formed by the type strain revealed a considerably higher cellular density and amount of matrix polysaccharides than single and binary biofilms formed by the isolated strains ( p <0.05). Similar OMP expression was detected for the several single strains and for the binary situation, not dependent on the hydrodynamic conditions. Binary biofilms revealed an equal coexistence of the isolated strains with apparent neutral interactions. In summary, the biofilms formed by the type strain represent, apparently, the worst situation in a context of control. The results obtained clearly illustrate the importance of considering strain variation and hydrodynamics in biofilm development, and complement previous studies which have focused on physical aspects of structural and density differences.